(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
We will focus on the effective use of STEAM technology in the unusual and integrated organization of lessons for elementary school students. Additionally, the study highlights the psychological benefits of STEAM education, such as improved spatial reasoning, collaboration, and resilience in young learners. The findings suggest that a well-designed STEAM curriculum, supported by interactive technology and student-centered learning approaches, can significantly enhance both academic and socio-emotional development in elementary school students.